Knowledge management in public organization : a study of knowledge transfer in immigration department Kota Kinabalu Sabah / Noraini Rasi - Rasi, Noraini (2008)
This study was carried out to ascertain the factors like organization structure, technology and people/human resource are exist in the knowledge transfer in the Immigration Department at Kota Kinabalu Sabah. The main focus of this study is to see if knowledge transfer occurs in the Immigration Department at Kota Kinabalu Sabah. A sample of 108 respondents of employees in Immigration department Kota Kinabalu Sabah was used for this study. Data was collected using questionnaires that given randomly to the respondents. Analysis of the data was done by using the spss version 13.0. The findings revealed that knowledge transfer were exist this study and employees do not face many problems in accessing knowledge transfer within their own units. The implications from the study suggest that the current approach such, organization structure, technology and human resource factor could help public organizations in Malaysia to become knowledge-based organizations.